2014
DOI: 10.1371/journal.pone.0090173
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Foraging by a Dominant Invasive Species to Decrease Its Competitive Ability

Abstract: Invasive species are a major threat to biodiversity when dominant within their newly established habitat. The globally distributed Argentine ant Linepithema humile has been reported to break the trade-off between interference and exploitative competition, achieve high population densities, and overpower nests of many endemic ant species. We have used the sensitivity of the Argentine ant to the synthetic trail pheromone (Z)-9-hexadecanal to investigate species interactions for the first time. We predicted that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 55 publications
4
12
0
Order By: Relevance
“…High pheromone concentrations prevent Argentine ants from establishing stable trails, thus limiting their ability successfully to forage and recruit greater numbers of conspecifics to resources in the area . Additionally, this treatment can also provide a competitive advantage for other resident ant species to increase their foraging, when directly competing with the Argentine ant for a specific food resource . Therefore, the potential exists for this synthetic trail pheromone to provide a management technique that, if successful, could reduce the risk of disruption to mealybug biological control and in doing so reduce the risk of plant pathogen spread.…”
Section: Introductionmentioning
confidence: 99%
“…High pheromone concentrations prevent Argentine ants from establishing stable trails, thus limiting their ability successfully to forage and recruit greater numbers of conspecifics to resources in the area . Additionally, this treatment can also provide a competitive advantage for other resident ant species to increase their foraging, when directly competing with the Argentine ant for a specific food resource . Therefore, the potential exists for this synthetic trail pheromone to provide a management technique that, if successful, could reduce the risk of disruption to mealybug biological control and in doing so reduce the risk of plant pathogen spread.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, it is possible that not all species elicit the same strong aggressive response from Argentine ants. In a previous experiment, we showed that Argentine ants react differently to competitors in field experiments and may chose to ignore or avoid some species if met under natural conditions (Westermann et al 2014).…”
Section: Discussionmentioning
confidence: 98%
“…In a previous experiment, we showed that Argentine ants react differently to competitors in field experiments and may chose to ignore or avoid some species if met under natural conditions (Westermann et al. 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Choe et al (2014) obtained similar results by mixing trail pheromone with an insecticide. Studies by Westermann et al (2014) suggested that long term disruption of foraging behavior of the Argentine ant with a synthetic trail pheromone might reduce their competitive ability, leading to collapse of populations in favor of less harmful, indigenous species. However, the difficulty of achieving significant control of ants by any of these techniques is attributable to the fact that colonies of ants are not fully dependent on their communal trail system for survival, but also can search independently and orient directly to food odors (Suckling et al 2010a).…”
Section: Discussionmentioning
confidence: 99%